2019
DOI: 10.1001/jamafacial.2019.0028
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Patterns of Age-Related Facial Bone Loss in Black Individuals

Abstract: IMPORTANCE Facial skeletal changes that occur with aging have critical importance to the aesthetics of the aging face and the field of facial rejuvenation. Patterns of bony change may differ based on race, but existing research is limited primarily to white or unspecified racial populations.OBJECTIVE To longitudinally document patterns of facial skeletal change among black individuals. DESIGN, SETTING, AND PARTICIPANTSThis retrospective case series study evaluated the medical records of patients treated at an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
4
3
0
Order By: Relevance
“…No significant difference was observed between age groups in men except for one group, which was similar to David's results among age groups [23]. However, in females, in this study, a significant relationship was observed between all groups, which indicates the stages of development in all periods in the condition of the bone in the growth of the midface in females.…”
Section: Discussionsupporting
confidence: 86%
“…No significant difference was observed between age groups in men except for one group, which was similar to David's results among age groups [23]. However, in females, in this study, a significant relationship was observed between all groups, which indicates the stages of development in all periods in the condition of the bone in the growth of the midface in females.…”
Section: Discussionsupporting
confidence: 86%
“…Our results suggest that pyriform aperture edges are being resorbed with age, which causes an increase in its horizontal and vertical parameters. It is consistent with the results of other authors, which showed signi cant changes of this kind 25,26,41,46,48,51,52 . In the examined medieval sample, the only signi cant result was the increase of the surface area in successive age groups.…”
Section: Pyriform Aperturesupporting
confidence: 93%
“…Some articles were excluded after full-text review for the following reasons: Lack of data referring to BBT [ 65 , 66 , 67 , 68 ], measurement not by (CB)CT scan [ 69 ] patients matching the exclusion criteria [ 19 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ], patients with implants [ 85 ], patients without teeth [ 86 ], data not displayed as mean and SD [ 56 ], site or kind of measurement not adequate [ 19 , 62 , 64 , 77 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ,…”
Section: Resultsmentioning
confidence: 99%